2012
DOI: 10.5897/ajb11.2939
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and citral content in lemongrass (Cymbopogon citratus) essential oil at three maturity stages

Abstract: The demand for lemongrass (Cymbopogon citratus) is for its high citral content. Early or delayed harvesting of lemongrass affected essential oil and citral content. The objective of the study was to determine the effects of three maturity stages at harvest of lemongrass on essential oil, chemical composition and citral contents. The lemongrass plant was planted using a randomized complete block design with four replications, at the University Agriculture Park, Universiti Putra Malaysia. The plants were harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 19 publications
7
76
0
3
Order By: Relevance
“…(65-85%), and citral has been reported to have antimicrobial effects, especially against MRSA methicillin resistant Staphylococcus aureus, where it was found to have similar activity as currents drugs like ampicillin [7]. Furthermore, high citral content is desirable in lemongrass oil, and has been the focus of studies to determine optimal plant harvesting times to obtain high citral levels [8]. The lot of oil that was tested in the present study had a citral content of nearly 80%, with the closely related compound geraniol as the next major constituent (GC-MS integration values not shown).…”
Section: Discussionmentioning
confidence: 99%
“…(65-85%), and citral has been reported to have antimicrobial effects, especially against MRSA methicillin resistant Staphylococcus aureus, where it was found to have similar activity as currents drugs like ampicillin [7]. Furthermore, high citral content is desirable in lemongrass oil, and has been the focus of studies to determine optimal plant harvesting times to obtain high citral levels [8]. The lot of oil that was tested in the present study had a citral content of nearly 80%, with the closely related compound geraniol as the next major constituent (GC-MS integration values not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Lemongrass is a type of plant that grows fast and grows optimally at an altitude of 50 -2700 meters above sea level. This tropical plant can grow well at a temperature of 10 -33 o C with enough sunlight [2,3]. The best lemongrass growth can be obtained in 700 -3000 mm rainfall areas with the rain frequencies spread evenly throughout the year [4].…”
mentioning
confidence: 99%
“…[3] Biological research has shown that the various chemical compounds in essential oil possess antibacterial, antifungal, analgesic, and mosquito repellent properties.It is consequently essential to investigate the chemical composition of lemon grass essential oil and evaluate the therapeutic potential of its volatile components.The chemical composition and pharmacological evaluation of lemon grass oil has been the subject of several studies over the years. [2] …”
Section: Introductionmentioning
confidence: 99%